(untitled) (Heritage, 2024)
Augmented (AR), virtual (VR), and mixed reality (MR) are types of immersive technologies that create different experiences by merging the physical world with digital or simulated reality. In recent years, these technologies have increasingly found their application in modern society in simulating a wide range of activities in a virtual environment. They are applied in business, health, education, military, but also in the field of culture and entertainment. From the point of view of the global economy, immersive technologies are becoming relevant at the world level, they are increasingly used as a way of learning, training or performance in almost all areas and thus directly contribute to global development. Immersive technologies can create an illusion by adding virtual content to real life, while the user’s awareness of not being part of the real environment is minimized. In a business context, these technologies can enable unique and pleasant experiences for consumers, who in an environment beyond reality can communicate with merchants, have multi-sensory interaction with brands, or the opportunity to be directly involved in product design. These experiences have an impact on consumer engagement and on their final purchase decision. Companies that decide to implement such technologies will be positioned in the minds of consumers as innovative, which can provide them with a competitive advantage in the market and higher revenues. However, the introduction of immersive technologies also carries certain risks. It is necessary to precisely determine the forms of technology that are adapted to a certain area or target market and to be informed about all the barriers they carry with them, such as the necessity of acquiring additional equipment (haptic gloves or headsets in the case of virtual reality). Immersive technologies are still in development, additional devices are expensive and there is uncertainty as to how widespread and accessible they will be to the public. However, their positive impact on the global economy is undeniable, and by reaching their full potential in the near future, these technologies will become an inseparable part of modern society.